Effects of mannan oligosaccharides on growth performance, nutrient digestibility, ruminal fermentation and hematological parameters in sheep - Zheng,Chen; Zhou,Juwang; Zeng,Yanqin; Liu,Ting (PeerJ, 2021)
Background Mannan oligosaccharides (MOS) are a promising feed additive in animal husbandry due to mainly improving animal health status. The purpose of this study was to investigate the effects of MOS on growth performance, nutrient digestibility, ruminal fermentation, and twelve hematological parameters in sheep. Methods Ninety-six healthy Hu rams with similar body weights were chosen and divided into four treatment groups (twenty-four rams in each group), in which four different doses of MOS were tested: 0%, 0.8%, 1.6% and 2.4% of the basal diet (on an as-fed basis). Results The results showed that supplementation dietary MOS did not affect feed intake, body weight, average daily weight gain, or ruminal short-chain fatty acids (SCFAs) concentration; the ratio of individual fatty acids to total SCFAs, the C2/C3 ratio, and the hematological parameters in the sheep were also unaltered (P > 0.05). Conversely, supplementation dietary MOS increased the dry matter, organic matter, crude protein, neutral detergent fiber, acid detergent fiber, and ash apparent digestibility (P < 0.05), and decreased the ruminal ammonia concentration in the sheep (P < 0.05), especially at a dose of 1.6%. Conclusions This indicates that supplementation dietary MOS improved nutrient utilization by the sheep and nitrogen metabolism in the rumen; however, the effects are too slight to interfere with the basal metabolism in the sheep.
Keywords: Digestibility; Growth performance; Mannan oligosaccharides; Ruminal fermentation; Sheep